Intra and Interreligious Dialogue before and after the Pandemic Distancing - Canta, Carmelina; Canta, Alba Francesca; Carbone, Chiara; Casavecchia, Andrea (Italian Sociological Review, 2022)
The article describes the results of a study that explores the effects of pandemic distancing on the dialogue experienced within religious communities and between believers of different religious backgrounds. The design of the research conducted on Key Informants identified among opinion leaders of different religious communities residing in Italy is presented, after having defined the concepts of dialogue, as a method of encounter/clash between identities, and of secularism, as a critical attitude and as a field of game on which to develop dialogue. The analysis of the interviews reveals dialogue practices that show a distinction between dialectical conversation and a dialogic conversation that made it possible to continue the dialogue during and after the pandemic distancing.